2023
DOI: 10.1111/imcb.12647
|View full text |Cite
|
Sign up to set email alerts
|

Defective N‐glycosylation in tumor‐infiltrating CD8+ T cells impairs IFN‐γ‐mediated effector function

Abstract: T cell-mediated antitumor immunity is modulated, in part, by N-glycosylation. However, the interplay between N-glycosylation and the loss of effector function in exhausted T cells has not yet been fully investigated. Here, we delineated the impact of N-glycosylation on the exhaustion of tumorinfiltrating lymphocytes in a murine colon adenocarcinoma model, focusing on the IFN-γ-mediated immune response. We found that exhausted CD8 + T cells downregulated the oligosaccharyltransferase complex, which is indispens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Restoration of N-linked glycosylation enhanced mitochondrial respiration again in CD4 + T cells exposed to malignant ovarian ascites (110). In addition to CD4 + T cells, Kim et al (111) demonstrated that deficient N-glycosylation impairs IFNg mediated effector function also in tumor-infiltrating CD8 + T cells, impacting the anti-tumor immune response. Mechanistically, tumor infiltrating and exhausted CD8 + T cells downregulate the oligosaccharyltransferase (OST) complex.…”
Section: The Influence Of the Tme On T Cell Functions Via The T Cell ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Restoration of N-linked glycosylation enhanced mitochondrial respiration again in CD4 + T cells exposed to malignant ovarian ascites (110). In addition to CD4 + T cells, Kim et al (111) demonstrated that deficient N-glycosylation impairs IFNg mediated effector function also in tumor-infiltrating CD8 + T cells, impacting the anti-tumor immune response. Mechanistically, tumor infiltrating and exhausted CD8 + T cells downregulate the oligosaccharyltransferase (OST) complex.…”
Section: The Influence Of the Tme On T Cell Functions Via The T Cell ...mentioning
confidence: 99%
“…OST complex is therefore indispensable for the N-glycosylation pathway. Interestingly, restoration of the OST complex complemented Nglycosylation that restored the IFNg production and alleviated CD8 + T cell exhaustion, consequently resulting in reduced tumor growth in preclinical models (111).…”
Section: The Influence Of the Tme On T Cell Functions Via The T Cell ...mentioning
confidence: 99%